2014
DOI: 10.3897/zookeys.406.6306
|View full text |Cite
|
Sign up to set email alerts
|

Ophiuroidea (Echinodermata) from coral reefs in the Mexican Pacific

Abstract: There are numerous and important coral reefs in the Mexican Pacific, but scarce studies of brittle stars conducted in these ecosystems. In this regard, this work provides the first annotated checklist of brittle stars associated with coral communities and reefs in the Mexican Pacific and an illustrated key to identify the species. We also provide taxonomic descriptions, spatial and bathymetric distributions and some important remarks of the species. We report a total of 14 species of brittle stars belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
17

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 41 publications
1
35
0
17
Order By: Relevance
“…In contrast Clark (1976) report the color matching between Ophiothela sp. and gorgonians and Granja-Fernández et al (2014) observed that O. mirabilis has a variety of colors (purple rosaceous, creamy, burgundy and yellow) that were correlated with the color of the hosts. This observation suggests that color may be an important camouflage for some lineages, but did not seem to be important to the yellow-orange lineage in Brazil, maybe because it possesses an innate predator deterrent such as chemical defense.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast Clark (1976) report the color matching between Ophiothela sp. and gorgonians and Granja-Fernández et al (2014) observed that O. mirabilis has a variety of colors (purple rosaceous, creamy, burgundy and yellow) that were correlated with the color of the hosts. This observation suggests that color may be an important camouflage for some lineages, but did not seem to be important to the yellow-orange lineage in Brazil, maybe because it possesses an innate predator deterrent such as chemical defense.…”
Section: Resultsmentioning
confidence: 98%
“…Ophiuroids collected and photographed in the field were identified as Ophiothela cf. mirabilis based on the key and description present in Granja-Fernández et al (2014), as well as on the original description by Verrill (1867). The specimens have a lobulated disk (disk diameter = 1.5-2.0 mm) with scattered round unequal grains, and with 6 arms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, specimens are similar in size, color, and overall morphology to other specimens in the Atlantic (Hendler et al 2012, Hendler andBrugneaux 2013). Nevertheless, even though the aforementioned morphological features are present in the species' description and used in an identification key (Verrill 1867, Granja-Fernández et al 2014, proper identification of Atlantic specimens remains provisional, due to morphological similarity and lack of taxonomic resolution in the genus Ophiothela (Clark 1976, Hendler andBrugneaux 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species were identified according to Granja-Fernández (2009) and Granja-Fernández et al (2014) for Ophiuroidea; Caso (1979Caso ( , 1987Caso ( , 1994 and Solís-Marín et al (2014) for Asteroidea; Caso (1980) for Echinoidea; and Solís-Marín et al (2009) …”
Section: Data Collectionmentioning
confidence: 99%